2002
DOI: 10.1038/oby.2002.72
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluoxetine Administration on Neuropeptide Y and Orexins in Obese Zucker Rat Hypothalamus

Abstract: GUTIÉ RREZ, ARANTZA, GONZALO SARACÍBAR, LUIS CASIS, ENRIQUE ECHEVARRÍA, VÍCTOR MAN-UEL RODRÍGUEZ, MARIA TERESA MACARULLA, LUIS C. ABECIA, AND MARÍA P. PORTILLO. Effects of fluoxetine administration on neuropeptide Y and orexins in obese Zucker rat hypothalamus. Obes Res. 2002;10: 532-540. Objective: The aim of this work was to study the potential involvement of neuropeptide Y (NPY) and orexins in the anorexigenic mechanism of fluoxetine in obese Zucker rats, assessing the effects of chronic fluoxetine treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
1
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 32 publications
5
17
1
7
Order By: Relevance
“…On the other hand, no significant effect of fluvoxamine was found on NPY immunostaining levels in ARC despite a trend toward a decrease in NPY. These data are supported by evidence reported by Gutierrez et al 15) and Dryden et al 14) for hyperphagic obese Zucker rats. Dryden et al 14) reported conflicting evidence for young Wistar rats: fluoxetine decreased NPY in PVN, increased NPY in ARC, and did not affect DMH.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…On the other hand, no significant effect of fluvoxamine was found on NPY immunostaining levels in ARC despite a trend toward a decrease in NPY. These data are supported by evidence reported by Gutierrez et al 15) and Dryden et al 14) for hyperphagic obese Zucker rats. Dryden et al 14) reported conflicting evidence for young Wistar rats: fluoxetine decreased NPY in PVN, increased NPY in ARC, and did not affect DMH.…”
Section: Discussionsupporting
confidence: 82%
“…16) A decrease of NPY levels in PVN is reportedly induced by fluoxetine. 14,15) These data corresponded with our results, which suggest that fluvoxamine-induced anorexia in our study resulted from reduction of NPY immunostaining in PVN. Those mechanisms might resemble those of fluoxetine.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations